2013
DOI: 10.1042/bj20121871
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-binding motif mimicry and cellular effects of a thieno[2,3-d]pyrimidine-based chemical inhibitor of atypical protein kinase C isoenzymes

Abstract: The aPKC [atypical PKC (protein kinase C)] isoforms ι and ζ play crucial roles in the formation and maintenance of cell polarity and represent attractive anti-oncogenic drug targets in Ras-dependent tumours. To date, few isoform-specific chemical biology tools are available to inhibit aPKC catalytic activity. In the present paper, we describe the identification and functional characterization of potent and selective thieno[2,3-d]pyrimidine-based chemical inhibitors of aPKCs. A crystal structure of human PKCι k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Furthermore, the recovery of polarity on reduction of PKCι in Ras- and ErbB2-transformed MDCK cells suggested that an overactive PKCι was responsible for this aberrant behaviour. In contrast, in the parent cell, loss of PKCι has been reported to trigger loss of polarity suggesting that in fact the PKCι dependence displays threshold behaviour (60,61,69). To test this, we manipulated gain and loss of function of PKCι in the parental MDCK cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the recovery of polarity on reduction of PKCι in Ras- and ErbB2-transformed MDCK cells suggested that an overactive PKCι was responsible for this aberrant behaviour. In contrast, in the parent cell, loss of PKCι has been reported to trigger loss of polarity suggesting that in fact the PKCι dependence displays threshold behaviour (60,61,69). To test this, we manipulated gain and loss of function of PKCι in the parental MDCK cells.…”
Section: Resultsmentioning
confidence: 99%
“…To assess this threshold, predicted catalytic behaviour of PKCι, we determined the response to the catalytic inhibitors CRT0066854, a recently described thieno[2,3-d]pyrimidine-based chemical inhibitor of aPKC (69), and Gö6983 (a pan PKC inhibitor) in H-Ras MDCK spheroids. Inhibitors were added on the day of seeding a single cell suspension in Matrigel and then replenished on alternate days for 6 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutagenesis of PKCι and Par3 was performed using QuikChange (Stratagene). Recombinant human PKC-iota kinase domain (PKCι KD ) was prepared using a baculovirus encoding residues 248–596 (GenBank: NM_002740.5), fused to a glutathione S-transferase (GST) tag as described previously (Kjaer et al., 2013). See Supplemental Experimental Procedures for a detailed description.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the ATP competitive aPKC inhibitors such as hydroxyphenyl-1-benzopyran-4-ones [36] and PKCzI257.3 [N-(4-((dimethylamino)methyl)-benzyl)-1H-pyrrole-2-carboxamide] [37] target both PKCζ and PKCι, but also other molecules unrelated to PKC. Other inhibitors show some isoform specificity include the thieno[2,3-d]pyrimidine-based compound CRT0066854 which was reported 4-fold more potent against PKCι than PKCζ [38]; and a 2-(6-phenylindazolyl)-benzimidazole derivative that shows increased inhibitory activity for PKCζ over PKCι [39]. …”
Section: Roles Of Atypical Pkcs In Pancreatic Cancer and Approaches Fmentioning
confidence: 99%